(untitled) (Ágora de Heterodoxias, 2015)
Olecranon bursitis is an articular disorder observed in dogs confined to hard surfaces or suffering repeated trauma on elbow joints. Although olecranon bursitis is a painless cosmetic problem; it can be difficult to resolve and it can concur with some clinical complications, such as infections and fibrosis. Treatments of olecranon bursitis through fluid aspiration and surgery are frequently ineffective approaches, since bursa refilling, bacterial infections, and wound dehiscence are common problems. Platelet rich plasma (PRP) is an autologous blood derived plasma fraction rich in platelet and growth factors, which are able to promote tissue repair. PRP has been used for the treatment of soft and hard tissues injuries. In this context, we report a case of chronic bilateral olecranon bursitis healing in a dog treated with autologous platelet rich plasma. Such as, it has been reported in human, and equine, our clinical observations indicates the favorable effect of using PRP in the healing of bursitis in dogs.